2011
DOI: 10.1080/17470218.2010.508532
|View full text |Cite
|
Sign up to set email alerts
|

Naming digits in a semantic blocking paradigm

Abstract: It is widely agreed that word numerals are processed similar to other words, and, thus, they can be named without semantic mediation. However, there is no consensus about Arabic digits. Although digits seem to have a preferential link to magnitude representation, there is some evidence indicating a possible asemantic route to access phonological information. In the present study, we used a semantic blocking paradigm to explore this question. In Experiment 1, participants were asked to name digits and pictures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
32
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 35 publications
9
32
1
Order By: Relevance
“…In summary, for other categories there was an interference effect produced by the blocked context relative to the mixed context for picture naming but not for word naming, which replicated previous studies (e.g., Damián et al, 2001;Herrera & Macizo, 2011;Kroll & Stewart, 1994). For numerical category, the results showed that the blocked context produced shorter RTs regardless of the notation, which replicated our previous work.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…In summary, for other categories there was an interference effect produced by the blocked context relative to the mixed context for picture naming but not for word naming, which replicated previous studies (e.g., Damián et al, 2001;Herrera & Macizo, 2011;Kroll & Stewart, 1994). For numerical category, the results showed that the blocked context produced shorter RTs regardless of the notation, which replicated our previous work.…”
Section: Resultssupporting
confidence: 90%
“…These results corroborated and extended our previous findings (Herrera & Macizo, 2011) by showing that this context effect did not depend on the stimuli that accompanied Arabic digits and number words. In particular, in the case of Arabic digits, a possible account for the absence of interference previously found could be in terms of response criterion adopted by the participants as function of the difficulty of the stimuli in the task (e.g., Lupker et al, 1997;Meyer et al, 2003;Taylor & Lupker, 2001).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Specifically, the authors asked whether the processing of banknotes required the accessing to semantic information. To this end, they adopted the blocking paradigm (Damian, Vigliocco, & Levelt, ; Kroll & Stewart, ; Levelt, ) to evaluate the semantic processing of two dimensions that define banknotes: the processing of pictures (Glaser, ) and the processing of numbers (Herrera & Macizo, , ; Roelofs, ). In this paradigm, participants name sequences of pictures in two situations: mixed and blocked.…”
Section: Introductionmentioning
confidence: 99%